"Rubber will not keep in this country": failed development in Benin, 1897-1921 - Fenske, J (University of Oxford, 2012)
Although Nigeria's Benin region was a major rubber producer in 1960, the industry faltered before 1921. I use labour scarcity and state capacity to explain why rubber did not take hold in this period. The government was unable to protect Benin's rubber forests from over-exploitation. Plantations found it difficult to recruit workers, and the government was unwilling to allow expatriates to acquire land. Colonial officials promoted the development of “communal” plantations, but these suffered due to labour scarcity and a state that was short on staff and equipment, and dependent on local chiefs.